Psychometric evaluation of the acute care nurses' job satisfaction scale‐revised - Yasin M. Yasin (14779381) (2022)
Aim The aim of this study was to validate a job satisfaction scale among acute care nurses in the context of Qatar. Design Cross‐sectional correlational survey. Methods A convenience sampling technique was used to recruit 295 acute care nurses between June 2021–September 2021. Exploratory factor analysis followed by confirmatory factor analysis was used for item reduction and convergent and discriminant validity evaluation. Pearson's correlations were conducted to evaluate the concurrent and convergent validity of the revised scale. Reliability was tested using several internal consistency indicators. Results A revised scale was proposed, the Acute Care Nurses Job Satisfaction Scale‐Revised (ACNJSS‐R) scale; it is composed of 13 items loaded on five factors. The composite reliability and the maximal reliability were >.7 for all factors. The study provides empirical support for the validity and reliability of the ACNJSS‐R scale. Other Information Published in: Nursing Open License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/nop2.1314 The University of Doha for Science and Technology replaced the now-former College of the North Atlantic-Qatar after an Amiri decision in 2022. UDST has become and first national applied University in Qatar; it is also second national University in the country.